Visualization and Predictive Analysis of Key Performance Indicators for Supply Chain Management - Mukesh Kumar ROHIL; Aditya SAXENA (Communications of International Proceedings, 2021)
Business Intelligence can be used to provide valuable insights into the working of a supply chain. We are advocating to use Parallel Coordinates for visualizing Key Performance Indicators of a Supply Chain. Further, we have used Multiple Linear Regression in Predictive Analytics to predict the value of Gross Margin Return on Investment based on Cash Conversion Cycle and Days Sales Outstanding. The model has been trained based on 10 years of simulated data and further predictions are made on Gross Margin Return on Investment. Predictive analysis is implemented to forecast the returns on investment which will form the basis of business decisions concerning investment on inventory in the subsequent time cycles. We have implemented Parallel Coordinates Plot for visualization of the Supply Chain Key-Performance Indicators for better side-by-side visualization and comparison of the trends, using the R Language.
Keywords: Business intelligence; data visualization; supply chain; predictive analytics; multiple linear regression; key performance indicators.